Comparison of subgrid-scale models for large-eddy simulation of hydrodynamic and magnetohydrodynamic channel flows. Issue 7 (1st July 2019) - Prinz, Sebastian; Schumacher, Jörg; Boeck, Thomas
Abstract : Purpose: This paper aims to address the performance of different subgrid-scale models (SGS) for hydro- (HD) and magnetohydrodynamic (MHD) channel flows within a collocated finite-volume scheme. Design/methodology/approach: First, the SGS energy transfer is analyzed by a priori tests using fully resolved DNS data. Here, the focus lies on the influence of the magnetic field on the SGS energy transport. Second, the authors performed a series of 18 a posteriori model tests, using different grid resolutions and SGS models for HD and MHD channel flows. Findings: From the a priori analysis, the authors observe a quantitative reduction of the SGS energy transport because of the action of the magnetic field depending on its orientation. The a posteriori model tests show a clear improvement because of the use of mixed-models within the numerical scheme. Originality/value: This study demonstrates the necessity of improved SGS modeling strategies for magnetohydrodynamic channel flows within a collocated finite-volume scheme.